Development of a patient-reported outcomes tool to monitor changes in joint health and wellbeing for young people with haemophilia B - Bladen Melanie; McDonagh Janet; McLaughlin Paul; Gooding Richard; Holder Kerry-Ann; Thind Sharon; Klooster Brittany; Shields Alan; Turner-Bowker Diane M.; Chatterton Kaitlin; Leso Allison; Volpi Connor; et al. (The Journal of Haemophilia Practice)
Early detection of joint bleeds is challenging yet critical for preserving joint health among individuals with haemophilia. This work explored early indicators of joint bleeds and young people with haemophilia B (YPwHB) self-monitoring practices to develop a joint health patient-reported outcome (PRO) tool for YPwHB aged between 8-25 years.